Implementation of Business License Services before and after The Job Creation Law - Dwi Puji Lestari; Fadhila Akbar Nurhakim; Maimunah Rusydah Istiqomah; Rhafie Ajie Firmansyah; Muhammad Valentino Lisoni Putra (Proceeding International Conference Restructuring and Transforming Law, 2024)
Indonesia as a nation upholds the idea of a welfare state, in which the state is thought to be crucial in guaranteeing the well-being of each and every individual. Prioritizing licensing services is crucial because of their implementation's setup of legal indicators and simplicity. Business actor licensing is crucial to the operation of the company. The passage of Law Number 11 of 2020 concerning Job Creation seeks to lower the complexity of licensing, which has been identified as one of the primary barriers to investment, boost investment, expand employment possibilities, and improve workforce capacities. There are several different types of licensing, such as certification, quota determination, registration of recommendations, and permissions. This methodology for research makes use of. Cette méthode de recherche utilise la recherche en bibliothèque. The licensing mechanisms in Indonesia before and after the Job Creation Law were very different, so it is hoped that after the law passes, entrepreneurs in Indonesia and abroad will be more motivated to invest and do business.